2018
DOI: 10.1038/s41598-018-24079-7
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the inhibitory activity of Chlamydomonas reinhardtii sulfated polysaccharides against α-Synuclein fibrillation

Abstract: α-Synuclein (α-Syn) is an intrinsically disordered presynaptic protein, whose aggregation is critically involved in Parkinson’s disease (PD). Many of the currently available drugs for the treatment of PD are not sufficiently effective in preventing progress of the disease and have multiple side-effects. With this background, efficient drug candidates, sulfated polysaccharides from Chlamydomonas reinhardtii (Cr-SPs) were isolated and investigated for their effect on inhibition of α-Syn fibrillation and dissolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…Some polysaccharides have been shown to stimulate neuroprotective effects in vivo, in different models for neurodegeneration [19]. Interestingly, a green algae polysaccharide was shown to have anti-PD activity through inhibition of α-Synuclein fibrillation [20,21]. Anti-PD activity was also recently determined for natural polysaccharides via increasing cellular autophagy [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some polysaccharides have been shown to stimulate neuroprotective effects in vivo, in different models for neurodegeneration [19]. Interestingly, a green algae polysaccharide was shown to have anti-PD activity through inhibition of α-Synuclein fibrillation [20,21]. Anti-PD activity was also recently determined for natural polysaccharides via increasing cellular autophagy [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, while no analysis of the extract composition of C. reinhardtii was performed in this work, there is some data published in peer-reviewed literature regarding bioactive compounds contained in extracts of this species. For example, Choudhary et al (2018) determined that ethanolic aqueous extracts of C. reinhardtii consisted to almost 70 % of carbohydrates with a high sulphate content, based on which the existence of sulphated polysaccharides in this green alga could be proven afterwards (Choudhary et al 2018;Kamble et al 2018;Vishwakarma et al 2019). In addition, Yao et al (2015) showed a high content of glycolipids for isopropanolic C. reinhardtii extracts.…”
Section: Effects Of the Enhanced Extracts On Virus Replication And Cellular Vitalitymentioning
confidence: 99%
“…In aqueous environments, ANS has a weak fluorescence and displays an emission of maximum at 500 nm. Upon binding to the hydrophobic patches of proteins it produces a blue shift in its emission wavelength and an increase in its fluorescence intensity the extent of which is dependent on the protein structure and milieu surrounding ANS [27]. In the presence of human TTR tetramer, ANS binds specifically to the thyroxine-binding sites within the hydrophobic cavity with a consequent increase in fluorescence intensity at about 480 nm [28].…”
Section: Determination Of Bme Binding To Ttrmentioning
confidence: 99%